BrExit or BritaIn: Is the UK more Attractive to Supervisors? An Analysis of Wage Premium to Supervision across the EU - Marco Biagetti; Antonio Giangreco; Leone Leonida; Sergio Scicchitano (Global Labor Organization (GLO), 2020)
We define the wage premium to supervision (WPS) as the extra wage that supervisors earn relative to their subordinates, and estimate it at different quantiles of wage distribution for 26 European economies, comparatively focusing on the UK. We find that, by compensating supervisory positions according to the wage, the WPS increases wage inequality across most of the economies studied. Further, over 10% of the WPS depends upon the economic context. Our results suggest that, regarding the WPS, the UK is more rewarding than the other economies. We discuss implications for immigration and policymakers in relation to the post-Brexit process.
Keywords: 330; Wage premium to supervision; Counterfactual density estimation; Role of economic context; Talent attraction; Brexit